KEABSAHAN ARBITRASE ONLINE SEBAGAI ALTERNATIF PENYELESAIAN SENGKETA - Mirah Novia Sari, I.G.A. Ayu; Sukranata, A.A. Ketut (Kertha Wicara : Journal Ilmu Hukum; Vol. 02, No. 02, April 2013)
Advances in technology cannot be offset by the development of the law is much slower, as seen from the lack of legal certainty regarding electronic arbitration, particularly against the validit Online arbitration as an alternative dispute resolution there is still disagreement about the legitimacy of online berarbitrase, writing this article using the Normative method is to relate the norms regarding the validity of the agreement terms, the terms validity and the validity of the award are assessed by an authentic legal force
Keywords: The arbitration, Online, Validity